Revitalisasi Musik Tradisional: Model Pembelajaran Tongkek Untuk Mengajarkan Konsep Fundamental Musik Di Sekolah Dasar - Nur Khair, Muhammad Alfian; Hary Murcahyanto; Sapriadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop and evaluate a music learning model based on the traditional Tongkek musical instrument for elementary school students. This study uses a qualitative approach with an educational ethnography design to reveal the implementation process, effectiveness, and meanings that emerge in learning. The results show that the use of the Tongkek musical instrument significantly improves students' musical understanding, especially in the aspects of rhythm and tempo. Students show better kinesthetic and auditory responses, as well as higher active engagement and learning motivation compared to conventional learning methods. In addition, Tongkek-based learning also encourages the growth of cultural awareness and strengthens students' local identity. The conclusion of this study is that the use of the traditional Tongkek musical instrument in music learning in elementary schools has proven effective in improving students' understanding of musical concepts, especially rhythm and tempo, as well as strengthening collaboration skills and cultural awareness. Despite challenges such as limited teacher training, this learning method holistically improves students' musical motivation and identity. Keywords: Music Education, Rhythm Learning, Tongkek, Traditional Instruments.